Biliary atresia: variability in evolution after kasai portoenterostomy. Report of two cases - Fiestas, Kerly (2025)
Background: Biliary atresia (BA) is a leading cause of neonatal cholestasis and the primary indication for liver transplantation in children. Its etiology is unknown and is characterized by the obliteration of the bile ducts, resulting in impaired bile flow, which manifests as jaundice, dark urine, pale stools, hepatomegaly, and/or splenomegaly. Kasai portoenterostomy (KP) can restore bile drainage, although its success decreases with increasing age at surgery. Case presentation: We report two infants who underwent intraoperative cholangiography followed by KP due to suspected BA. Liver biopsies confirmed the diagnosis. Outcomes were influenced by the timing of surgery: one patient, who underwent surgery at a later age, experienced an unfavorable course and required early liver transplantation. Conclusion: These cases highlight age at KP as a key determinant of BA outcomes. Late diagnosis remains a challenge despite existing policies at various levels of care, emphasizing the need to strengthen national screening programs.